A possible jet and corona configuration for Swift J1727.8–1613 during the hard state - Peng, Jing-Qiang; Zhang, Shu; Shui, Qing-Cang; Zhang, Shuang-Nan; Chen, Yu-Peng (Journal of high energy astrophysics, 2025)
Swift J1727.8–1613 is a black hole X-ray binary that differs from other black hole X-ray binaries in that it has an extra hard component in addition to a reflection component. We perform spectral analysis with simultaneous Insight-HXMT, NICER and NuSTAR observations when the source was in the hard and hard intermediate states. For the presentation of the extra components, we investigate the correlation between the relxill parameters. We find that the correlation between the spectral index and the reflection fraction is consistent with MAXI J1820+070 when the jet dominates the reflection. This provides the second sample to have such a correlation during an outburst. Interestingly, when the reflection component is attributed to the corona, the spectral fit results in a small reflection fraction and the correlation between the spectral index and reflection fraction is in agreement with the overall trend built-in You et al. (2023) with a large sample of outbursts from other X-ray binaries. Hence Swift J1727.8–1613 turns out to be the first sample to bridge the MAXI J1820+070 to the majority of X-ray binaries according to the dual correlations observed between the spectral index and the reflection fraction. We speculate that a configuration of a jet plus a hot inner flow may account for this peculiar outburst behavior of Swift J1727.8–1613.